AN ANALYSIS OF ADDED VALUE AND MARKETING OF PROCESSED CATFISH (Clarias sp.) PRODUCTS IN HANGTUAH VILLAGE PERHENTIAN RAJA SUBDISTRICT KAMPAR REGENCY RIAU PROVINCE - Toni Ariyanto; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on June 2015 in Hangtuah Village Perhentian Raja Subdistrict Kampar Regency Riau Province. The objectives of the research are to identify the processed products in the Hangtuah Village, analyze middle costs, added value, value added ratio, margins and products recompense in Hangtuah Village, and its marketing systems. The survey methode was used by case study in which respondents were determined by purposive sampling technique. The results showed that there were three processed Catfish (Clarias sp.) products namely meatballs, nuggets, and crackers. The costs of meatballs ingredients/production is Rp. 180,000, nugget is Rp. 180,000, and crackers is Rp. 84,000. The middle costs in meatballs is Rp. 62,500, nuggets is Rp. 116.500, and crackers is 314.000. Value added meatballs processing is 36. 200/Kg, value added ratio is 40.2222%, margin is Rp. 50,000/Kg, recompense of meatballs processing is Rp. 32.567/Kg. Value added nugget processing is Rp. 64.112/Kg, value added ratio is 49.3169%, margin is Rp. 90,000/Kg, recompense of nugget processing is Rp. 60.479/Kg. While value added crackers processing is Rp. 19.448/Kg, value added ratio is 50.6458%, margin is Rp. 34,400/Kg, and recompense of meatballs processing is Rp. 15820.9 / Kg. Keywords: Added Value, Processing, Margins, Marketing